Dari Warisan Leluhur Hingga Industri Kreatif: Menelisik Sejarah, Makna Filosofis, Dan Pengembangan Ekonomi Songket Silungkang Duo Di Kota Sawahlunto - Irvan Rasyid; Jenny Meylani Putri; Adinda Angguni Putri; Lasmini .; Nur Amidah Ramadani; Zul Afdal (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study analyzes the history, philosophical meaning, and economic development of Songket Silungkang Duo in Sawahlunto City. Using a qualitative literature study approach, data were analyzed using the Miles and Huberman interactive model. The results show that Songket Silungkang is a cultural heritage passed down from generation to generation as an adaptive response of the community to difficult geographical conditions. In Silungkang Duo, the weaving tradition is maintained by nine active artisans who received loom assistance in 2019. The motifs of pucuak rabuang, kaluak paku, and itik pulang patang contain philosophical meanings about usefulness, humility, togetherness, as well as the values of beauty, sacredness, perseverance, precision, and patience. The government, through the Cooperatives and Trade Office, has been conducting weaving training since 2012, which has succeeded in increasing the number of artisans and diversifying products. Analysis of Granovetter's social attachment theory shows that the relationship between artisans and their landladies is not only economic but also social. Parsons' AGIL scheme analysis shows that empowerment programs fulfill the functions of adaptation, goal achievement, integration, and pattern maintenance. Challenges such as low wages and declining interest from the younger generation are still faced, but opportunities are open through government support, digital technology, and the global market. The development of songket as a creative economy is inseparable from an understanding of its history and philosophy